DESIGN OF METAVERSE LEARNING ENVIRONMENTS TO ENHANCE ANALYTICAL THINKING FOR PRIMARY ONE LEVEL - Sirichokchaitrakool, Sirisukr; Namboonrueang, Narian; Nunklang, Pawanan (Journal of Education and Innovation, 2025)
This research was conducted to satisfy the following objectives: 1) To examine the results of learning environments created using the Metaverse, 2) To evaluate the analytical thinking capabilities of each student, 3) To examine the learning outcomes of the lessons, 4) To assess feedback from first-grade students at Khon Kaen University Demonstration School, Faculty of Education, comprising 38 individuals, during the first semester of the 2024 academic year. Instruments used in this research consist of learning environment design based on Metaverse’s available tools, an analytical thinking test and an academic achievement evaluation test. Qualitative data was analyzed using descriptive analysis, and the statistics used included percentages, means, and standard deviations. The results of this research are as follows; The Metaverse learning environment includes key components: Problems and missions, Learning resources, Foundational Scaffolding, Collaboration, and Coaching. Analytical thinking capability evaluation shows that 31 students (81.58%) achieved an average score of 11.50, equating to 76.66%. In term of learning results, 30 students (78.95%) achieved an average score of 15.63, equating to 76.30%. Students’ feedback indicates that the contents are appropriate and easy to understand. In term of design, a clear, readable, colorful, and engaging font has been included. The problem situations and learning tasks incorporated questions that stimulated analytical thinking and supported self-directed knowledge construction. Students were able to share and exchange their ideas. Lastly, different problem-solving situations enabled students to gain deeper understanding of the content.